Ethical Challenges of Multicultural Marketing - Remizov, Gleb; Müller, Karel B., 1972-; Křečková Kroupová, Zuzana, 1972-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
In the modern world society reacts sharply to unethical behavior of companies. The goal of the thesis is to analyze the problems of ethically-driven decisions of companies, provide the reader with a secondary research of the topic and to investigate and compare different advertising campaigns in order to highlight mistakes and attempt to develop a strategy to avoid them in the future cases with an addition of marketing strategies’ adaptation to contemporary realities.The theoretical part describes ethics, some of the ethical theories and explains the role of ethics in marketing. The thesis provides examples of companies’ marketing successes and failures.
Vedoucí práce: Karel Müller
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses